1997
DOI: 10.1046/j.1471-4159.1997.68020710.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Lubeluzole Is Mediated Through the Signal Transduction Pathways of Nitric Oxide

Abstract: Neuronal survival after ischemic injury is determined through the induction of several biological pathways. We examined whether lubeluzole, an agent efficacious in both clinical and experimental models of cerebral ischemia, modulated the signal transduction mechanisms of nitric oxide (NO), a downstream mediator of anoxic neurodegeneration. Both pretreatment [NO survival = 23 ± 3%, NO/lubeluzole (750 nM) survival = 63 ± 2%, p < 0.001] and coadministration [NO survival = 25 ± 3%, NO/lubeluzole (750 nM) survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…As an example, externalization of membrane PS residues occurs in neurons during anoxia (Maiese, 2001;Maiese and Boccone, 1995;, nitric oxide exposure (Chong et al, 2003f;Maiese et al, 1997), and during the administration of agents that induce the production of reactive oxygen species, such as 6-hydroxydopamine (Salinas et al, 2003). Membrane PS externalization on platelets also has been associated with clot formation in the vascular cell system (Leytin et al, 2006).…”
Section: Epo and Cellular Oxidative Stressmentioning
confidence: 99%
“…As an example, externalization of membrane PS residues occurs in neurons during anoxia (Maiese, 2001;Maiese and Boccone, 1995;, nitric oxide exposure (Chong et al, 2003f;Maiese et al, 1997), and during the administration of agents that induce the production of reactive oxygen species, such as 6-hydroxydopamine (Salinas et al, 2003). Membrane PS externalization on platelets also has been associated with clot formation in the vascular cell system (Leytin et al, 2006).…”
Section: Epo and Cellular Oxidative Stressmentioning
confidence: 99%
“…Accordingly, we next mimicked the in vivo ischemia-induced pyramidal neuron death by using NO-related SNP-induced toxicity (Maiese et al, 1997) in cultured hippocampal neurons and test the effects of SNP and Bay K8644 on the currents.…”
Section: Downregulation Of L-type Camentioning
confidence: 99%
“…Lubeluzole (Figure 1), a novel benzothiazole compound which currently has tested antiischemic in clinical and preclinical studies has been shown to attenuate growth of ischemic damage as well as its density in the periphery of a photochemically induced neocortical infarct in rats [19]. It is a NOS inhibitor, which in addition decreases glutamate release and blocks sodium and calcium channels [20,21]. Another example of an analogue with an aminothiazole moiety is riluzole (Figure 1), a novel neuroprotective drug that is approved worldwide for the treatment of amyotrophic lateral sclerosis and is active in a wide variety of experimental models of neurodegenerative diseases, including toxin-induced models of PD in rodent and primate [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%